Surveying the Relevance of the Critical Success Factors of Agile Transformation Initiatives from a Project Management Perspective - Fortuna, Alessandra; Mattos, Claudio Saraiva; Andrade, Álan Júnior Da Cruz; Ramos, Luiz Felipe; Dutra, Eliezer; Santos, Rodrigo Pereira Dos; Santos, Gleison (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2023)
Background: Agile methods and practices have been consistently adopted in recent years as alternatives to traditional software development processes to address the ever-changing needs of IT organizations. In a previous systematic mapping study, we identified twelve critical success factors of agile transformations from a project management perspective. Objective: In this paper, we investigate how practitioners perceive the relevance of these factors and whether other factors should be considered. Method: We conducted a survey research involving project managers from several organizations undergoing agile transformations. Results: The participants’ perceptions provided valuable insights into the relevance of the critical success factors. Additionally, we identified five new critical success factors: organizational ambidexterity, use of tools and automation, breaking down organizational silos, team commitment, and alignment of organizational goals and expectations. These newly identified factors contribute to a more comprehensive understanding of organizations’ challenges during an agile transformation. Based on the results and the literature, we formulated three propositions representing recommendations that can foster agile transformation. Conclusions: The evidence gathered in this study indicates that the factors investigated previously are highly relevant. Moreover, organizations should consider them to enhance the chances of success of agile transformation initiatives.